2017
DOI: 10.1002/cne.24187
|View full text |Cite
|
Sign up to set email alerts
|

A central mesencephalic reticular formation projection to medial rectus motoneurons supplying singly and multiply innervated extraocular muscle fibers

Abstract: We recently demonstrated a bilateral projection to the supraoculomotor area from the central mesencephalic reticular formation (cMRF), a region implicated in horizontal gaze changes. C-group motoneurons, which supply multiply innervated fibers in the medial rectus muscle, are located within the primate supraoculomotor area, but their inputs and function are poorly understood. Here, we tested whether C-group motoneurons in Macaca fascicularis monkeys receive a direct cMRF input by injecting this portion of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 99 publications
(178 reference statements)
4
26
0
Order By: Relevance
“…It should be noted, however, that we found significant physiological differences that could be in accordance with previous morphological studies (20)(21)(22)(23). The analysis of discharge characteristics revealed noticeably lower firing rates in MIF motoneurons compared with SIF motoneurons.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…It should be noted, however, that we found significant physiological differences that could be in accordance with previous morphological studies (20)(21)(22)(23). The analysis of discharge characteristics revealed noticeably lower firing rates in MIF motoneurons compared with SIF motoneurons.…”
Section: Discussionsupporting
confidence: 91%
“…Similar conclusions have been proposed after anterograde labeling from several premotor areas to SIF and MIF oculomotor motoneurons in monkeys (20). More recent studies have also found differences in afferents to the two motoneuronal types (22,23). Our data, however, are not in accordance with the division of motoneurons into "slow" versus "fast" or "tonic" versus "phasic," nor in a segregation based on the type of eye movement in which they participate (15,20,21,31).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The SCi has anatomical connections to the parasympathetic and sympathetic pathways to change pupil size (11). The SCi connects to a downstream parasympathetic structure, the Edinger-Westphal (EW) nucleus, mainly via projections through the central mesencephalic reticular formation (40,41). The EW nucleus projects to the ciliary ganglion with excitatory and inhibitory connections (42) and can therefore produce constriction and dilation.…”
Section: Discussionmentioning
confidence: 99%
“…The characteristics of these fiber types differ considerably (see Spencer and Porter, 2006 for review) and there are also differences in the motor neurons that innervate the two fiber types. In primates, SIF motoneurons are large cells found within the extraocular motor nuclei, while MIF motoneurons are small cells found just outside the nuclear borders (Wasicky et al, 2004;Erichsen et al, 2014;Bohlen et al, 2017). In cat, medial rectus SIF and MIF motoneurons are both found within III, albeit in anatomically separate subgroups, and MIF motoneurons are smaller (Bohlen et al, 2016).…”
Section: Mif and Sif Motoneuronal Populationsmentioning
confidence: 99%